WHAT WILL PERU´S WORKING ENVIRONMENT IN 2030 - Zilberman, Jack (2020)
The fourth industrial revolution assumes an exponential acceleration of information technologies that will impact industries and different types of professional work. Robots will execute operative jobs but the interpersonal skills of human beings will continue to be essential in various complex tasks. In Latin America there are opportunities resulting from the access to technologies; however, there are also disadvantages; because of labor market inadequacy. In the Peruvian case, local authorities have the responsibility to create those conditions that would allow companies and workers to develop the skills deemed  necessary for an adequate performance in future business scenarios. And, as far as education goes, it is important for students to develop their own ability to solve problems autonomously.